2021
DOI: 10.35790/msj.2.2.2021.32596
|View full text |Cite
|
Sign up to set email alerts
|

Perbandingan Leukosituria, Nitrit, Leukosit Esterase dengan Kultur Urin dalam Mendiagnosis Infeksi Saluran Kemih pada Anak

Abstract: Urinary tract infection (UTI) in children is the most common infection after upper airway infection. The diagnosis of UTI is based on urine culture, however, this examination takes a longer time and is quite expensive. Therefore, the diagnosis of UTI can also be confirmed by using leukocyturia, nitrite, and leukocyte esterase tests although they can not replace urine culture as the gold standard. This study was aimed to determine the accuracy of positive leukocyturia, positive nitrite, positive leukocyte ester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…So it can be concluded that diagnosing UTI with nitrite is not very significant, because even though the nitrite results are negative, it cannot rule out the absence of bacteriuria because it can be caused by urinary tract infections by bacteria that do not produce nitrite. Nitrite-forming bacteria are E. coli, Proteus, Klebsiella, Aerobacter, Citrobacter, Salmonella, some Enterococci, Staphylococci, Pseudomonas, Serratia marcescens while bacteria that do not form nitrite are Streptococcus faecalis, Gonococcus, Tuberculosis, Shigella, urine has not been in the bladder long enough, or excessive diuresis (Rosida and Pratiwi, 2019). In this study, a weak and unidirectional significant relationship was found between the results of the examination of leukocyte esterase and nitrite.…”
Section: Figure 2 Leukocyte Esterase Urinalysis Examination and Numbe...mentioning
confidence: 49%
See 2 more Smart Citations
“…So it can be concluded that diagnosing UTI with nitrite is not very significant, because even though the nitrite results are negative, it cannot rule out the absence of bacteriuria because it can be caused by urinary tract infections by bacteria that do not produce nitrite. Nitrite-forming bacteria are E. coli, Proteus, Klebsiella, Aerobacter, Citrobacter, Salmonella, some Enterococci, Staphylococci, Pseudomonas, Serratia marcescens while bacteria that do not form nitrite are Streptococcus faecalis, Gonococcus, Tuberculosis, Shigella, urine has not been in the bladder long enough, or excessive diuresis (Rosida and Pratiwi, 2019). In this study, a weak and unidirectional significant relationship was found between the results of the examination of leukocyte esterase and nitrite.…”
Section: Figure 2 Leukocyte Esterase Urinalysis Examination and Numbe...mentioning
confidence: 49%
“…Klebsiella pneumoniae is one of the causes of nosocomial infections with its main transmission originating from the gastrointestinal tract and is also closely related to the hand hygiene of medical personnel on duty, Klebsiella pneumoniae in the hospital area has the ability to spread rapidly, making it the most common cause of nosocomial infections (Andari et al, 2021). Pseudomonas sp which often infects patients with urinary catheters (Rosida and Pratiwi, 2019). Gram-positive bacteria that cause UTI in this study are Staphylococcus haemolyticus, Staphylococcus aureus.…”
Section: Figure 2 Leukocyte Esterase Urinalysis Examination and Numbe...mentioning
confidence: 83%
See 1 more Smart Citation